Evaluating the chip formation process and machining performance during orthogonal cutting using bio‐based metalworking fluids - Amiril Sahab, Abdul Sani; Shahandzir, Baharom; Zubaidah, Zamri (Malaysian Tribology Society (MYTRIBOS), 2024)
Metalworking fluids (MWFs) serve to cool and lubricate tools, but commercial MWFs harm the environment and pose health risks due to mineral oil content. Vegetablebased MWFs are being researched as alternatives for their superior properties and biodegradability. A Quick Stop Device (QSD) is used to monitor chip formation during metalworking processes that are lubricated with vegetable-based minimal quantity lubrication (MQL) to evaluate the efficiency of the lubricant. Experimental comparison between vegetable oils and synthetic esters during stainless steel turning showed MQL, combining air and cutting fluid, as a better alternative to flood coolant systems. Crude Tamanu Oil (CTO), Crude Jatropha Oil (CJO), and palm olein (RBDPO) led to Build Up Edge (BUE) development, indicating less effectiveness compared to Synthetic Ester (SE). Lubricant application reduces friction, improving surface quality and formed short continuous chips during turning.